Field Evaluation of Trichoderma viride for the Management of Rice Leaf Blast Disease in Pyuthan District, Nepal - Bhusal, N. R.; Acharya, B.; Devkota, A. R.; Shrestha, J. (Journal of the Institute of Agriculture and Animal Science, 2018)
A field experiment was conducted at Prime Minister Agriculture Modernization Project (Zone office), Bijuwar, Pyuthan from 18th April, 2017 to 12nd September, 2017 to evaluate the efficacy of Trichoderma viride in the management of leaf blast diseases of rainy season rice under field conditions. The experiment was laid out in two factors factorial Randomized Complete Block Design with five replications. The treatment consisted of two varieties of rice of which one is improved and resistant to blast disease (Sabitri) and another is local (Radha 7) and two rates of Trichoderma viride (5 ml/lit. and 0 ml/lit.). The leaf blast disease was scored three times using the disease rating scale 0-9 given by IRRI, 2002 from 75 DAT to 85 DAT at 5 days interval. The disease incidence, severity and AUDPC value were calculated and analyzed by using RSTAT. The variety factor and Trichoderma viride factor varied significantly for leaf blast incidence, severity and AUDPC, however, the interaction of variety and Trichoderma viride factor varied significantly only in AUDPC value. Disease incidence, severity and AUDPC were found least in Sabitri in comparison to Radha 7. T. viride had significant role in reducing the disease incidence, severity and AUDPC value. The interaction of Sabitri and Trichoderma viride treatment was found best with the mean AUDPC value being the least 3.228. So, the application of Trichoderma viride was found efficient for leaf blast management and it is more effective when applied along with an improved and resistant variety.